INITIAL DEVELOPMENT OF EUCALYPTUS ACCORDING TO DIFFERENT DESICCATION PERIODS OF SIGNALGRASS - Graat, Y. [UNESP]; Bacha, A. L. [UNESP]; Nepomuceno, M. P. [UNESP]; Alves, P. L. C. A. [UNESP] (Univ Federal Vicosa, 2018)
This study aimed at evaluating the effects of different desiccation periods of Urochloa decumbens on the initial development of Eucalyptus urograndis (clone C-219H). The experiment was conducted in 100 liter concrete boxes, previously filled with Dark-Red Latosol. U. decumbens was sown in all plots, except for the control sample without covering. After 95 days from sowing, the herbicide glyphosate (dose of 1,424 g a.e. ha(-1)) was sprayed at intervals of 0 (Apply-Plant), 7, 14, 21, 28 and 35 days before eucalyptus planting, plus a control sample without covering, totaling seven treatments. A completely randomized design with six replications was used. Eucalyptus plants were evaluated 30, 60 and 90 days after planting (DAP), when the height of the plants and the diameter of the stem were determined. At the end of the experimental period (90 DAP), the leaf area and the dry matter of leaves and stem were measured. It is possible to conclude that the Apply-Plant modality was harmful to some of the eucalyptus characteristics (E. urograndis - C-219H), while planting the seedlings in periods over 14 days after the desiccation of U. decumbens plants promoted a better development of the culture.
Keywords: Eucalyptus urograndis; Urochloa decumbens; plant cover; allelopathy